The Role of Personalization in Digital Marketing: A Study of Consumer Attitudes and Purchase Intentions. (Entrepreneurship Journal for Finance and Business, 2024)
The digital era has completely changed how companies communicate with their customers, especially when it comes to marketing. The goal of "The Role of Personalization in Digital Marketing: A Study of Consumer Attitudes and Purchase Intentions" is to get insight into how consumers view digital marketing that is tailored to them, A Pearson correlation coefficient and a five-point Likert scale were used in this study to measure customer attitudes and how they affected purchase intentions. The study instrument displayed strong internal consistency and dependability, as seen by its Cronbach's Alpha coefficients, which varied from 0.724 to 0.901. The results indicate that, in general, tailored digital marketing methods have a favourable effect on customer attitudes and purchase intentions; nevertheless, further research is necessary to fully understand the consequences for consumer trust.